Teacher pleaser or potentially gifted? - Mittan, Ken (Hawker Brownlow Education, 1990)
This handbook will assist you in determining an answer to the question: Is this student potentially gifted or a teacher pleaser? The need is not to identify really bright/gifted students but to distinguish between the potentially gifted student and the te.